About problem analysis of sufficiency of technology stack for solution development in field of industrial automation - E. Yu. Andieva; E. M. Guryeva; V. A. Mikhailov (Омский научный вестник)
The problem of forming effective «digital» organization of the base of engineering knowledge of IT-projects specifies objective to form special environment for accumulating the base of the best engineering practices. The article contains extensive analysis of technology platforms used to provide the ecosystem of forming the base of engineering practices in field of digital solutions I4.0. The article is devoted to main problems in provision of ecosystem of solution development of industrial automation taking into account features of the global changes in the field of digital engineering practices. It is revealed in studies that there are number unsolved challenges related to being far behind in provision of ecosystem’s development of integral solutions at industrial automation. Solutions that encompassed majority of system life cycle processes are foreign and proprietary.